A taxonomic revision of the southern African endemic genus Gazania (Asteraceae) based on morphometric, genetic and phylogeographic data - Howis, Seranne (Rhodes University, Faculty of Science, Botany Department, 2007)
Gazania is a small genus of the subtribe Gorteriinae, tribe Arctoteae, that is endemic to southern Africa. The genus was last revised in 1959 by Roessler, who noted that delimitation of the species of Gazania can be "extraordinarily difficult" . Morphometric data was collected to test the reality of the 16 species as delimited by Roessler, who based species boundaries on morphological characters. Only six taxa were found to be morphologically distinct, while the remaining samples showed no species cohesion. DNA sequence data from two nuclear spacer regions (ITS and ETS) and four chloroplast noncoding regions (the trnL and rpS16 introns, and the psbA-trnH and trnL-F spacers) of 43 samples were utilised to create a species level phylogeny and to investigate correlations between genetically delimited units and morphologically defined taxa. DNA sequence data reveal that seven species (as delimited by Roessler) are morphologically and genetically distinct. The remaining nine of Roessler's species fall into a morphologically and genetically overlapping continuum that forms an ochlospecies. Phylogeographic methods (based on an expanded ITS and ETS DNA sequence data set from 169 samples) were employed to further resolve the limits of species, with special focus on the clades within the ochlospecies. These genetically defined clades were correlated with their geographical distributions, and in combination with molecular dating techniques, used to elucidate the recent climatic or environmental factors that may have shaped the phylogeographic structure of the genus. Phylogeographic patterns and molecular dating reveals that the genus Gazania is an example of a South African endemic clade that has undergone episodic cladogenesis in response to fluctuating climatic conditions over the last seven million years. The ochlospecies within Gazania is a result of repeated cycles of climate driven isolation in refugia and subsequent expansion and hybridization events during the Pliocene and Pleistocene. Comparisons with phylogeographic studies on other organisms reveal a common pattern indicative of the presence and evolutionary importance of an ancestral refugium in the arid Richtersveld / Namib region of southern Africa.
Keywords: Compositae; Plant genetics; DNA Endemic plants -- South Africa; Plant ecology -- South Africa